A Role for the Androgen Metabolite, 5alpha Androstane 3beta, 17beta Diol (3β-Diol) in the Regulation of the Hypothalamo-Pituitary–Adrenal Axis - Handa, Robert J.; Sharma, Dharmendra; Uht, Rosalie M. (Frontiers in Endocrinology, 2011)
Activation of the hypothalamo-pituitary-adrenal (HPA) axis is a basic reaction of animals to environmental perturbations that threaten homeostasis. These responses are ultimately regulated by neurons residing within the paraventricular nucleus of the hypothalamus (PVN). Within the PVN, corticotropin-releasing hormone (CRH), vasopressin (AVP) and oxytocin (OT) expressing neurons are critical as they can regulate both neuroendocrine and autonomic responses. Estradiol (E2) and testosterone (T) are well known reproductive hormones, however, they have also been shown to modulate stress reactivity. In rodent models, evidence shows that under some conditions E2 enhances stress activated ACTH and corticosterone secretion. In contrast, T decreases the gain of the HPA axis. The modulatory role of testosterone was originally thought to be via 5 alpha reduction to the potent androgen, dihydrotestosterone, whereas E2 effects were thought to be mediated by both estrogen receptors alpha (ERα) and beta (ERβ). However, DHT has been shown to be metabolized to the ERβ agonist, 5alpha- androstane 3beta,17beta diol (3b-Diol). The actions of 3β-Diol on the HPA axis are mediated by ERbeta which inhibits the PVN response to stressors. In gonadectomized rats, ERbeta agonists reduce CORT and ACTH responses to restraint stress, an effect that is also present in wild-type but not ERbeta knockout mice. The neurobiological mechanisms underlying the actions of ERbeta to alter HPA reactivity are not currently known. CRH, AVP and OT have all been shown to be regulated by estradiol and recent studies indicate an important role of ERbeta in these regulatory processes. Moreover, activation of the CRH and AVP promoters have been shown by 3β-Diol binding to ERbeta and this is thought to be through alternate pathways of gene regulation. Based on available data, a novel and important role for 3beta Diol in the regulation of the HPA axis is suggested.